Complex Fibonacci p-Numbers - Tasci, Dursun; Yalcin, Feyza (Communications in Mathematics and Applications, 2014)
In the present paper, the complex Fibonacci p-numbers are defined by two-dimensional recurrence relation and some results are obtained.